Impact of Automobile Recalls on Stock Prices: A Study in the Indian Context. Issue 2 (April 2018) - Singh, Jagandeep
Not so long ago, 'product recalls' in the Indian automobile sector were a novelty. The defective vehicles were repaired as part of the after-sales service. In the absence of a strong regulatory framework, the manufacturers were under no obligation to proactively initiate product recalls. The introduction of a voluntary code on product recalls by the Society of Indian Automobile Manufacturers (SIAM) in 2012 and introduction/amendments in the existing legal regimen of the country in recent years have led companies to take more than just baby steps towards product recalls. Product recalls are a case of management failure. There is a need for gauging the impact of this failure on the stock price of the manufacturers, especially in the Indian context where the recall phenomenon is poised to gain further momentum. The event study methodology is a widely used approach to assess the impact of a particular event/announcement on the stock price. This methodology was used in the present study to gauge whether abnormal stock returns accrued to the manufacturers during 13 product recall announcements made in the Indian automobile sector between 1 January 2010 and 31 December 2015. The study found that product recall announcements generated small and statistically insignificant cumulative abnormal returns (CAR) of –0.02 per cent in the (–1, +1) event window, 0.92 per cent in the (–2, +2) event window and 1.70 per cent in the (–5, +5) event window. The study found no substantial or statistically significant difference in the CAR generated during big recalls and small recalls. Furthermore, the study found little evidence that CAR generated during recalls where defective component(s) in the vehicle were repaired is positive as compared to CAR generated when such component(s) were replaced.